Shakespeare and the legal imagination - Ward, Ian (Butterworths, 1999)
This work offers an analysis of constitutional law, examining Shakespeare's plays as legal texts. Professor Ward uses the plays as a starting point to investigate the development of constitutional ideas such as sovereignty, commonwealth, conscience and moral law, and the art of government. In the developing area of law and literature, this book examines how Shakespeare's work offers a rich source of textual material on legal subjects.